PEMBELAJARAN FIQIH BERBASIS KITAB KUNING MUKHTASAR ABI SUJA DI MTS DARUN NAJAH KARANGPLOSO - Qurrotul A’yun; Moh. Mansur Fauzi (Journal Islamic Studies, 2025)
Islamic boarding schools are the first Islamic educational institutions in Indonesia that still exist today, with a main focus on teaching the yellow book. Despite advanced technology, MTs Darun Najah Karangploso still uses the yellow book teaching method which has not changed much, and yellow book studies there do not yet have a systematic and detailed plan. Based on this description, the problem that can be formulated is a) How is the implementation of fiqh learning using the Mukhtasar Abi Suja book for class VIII students in Darunnajah at Mts Darun Najah Karangploso?, b) What are the supporting factors and inhibiting factors in the implementation of fiqh learning using Mukhtasar Abi Suja's book and how to overcome these inhibiting factors? The type of research used is descriptive qualitative research with the type of field research. The data collection method is by using observation, interviews and documentation. Meanwhile, the technical data analysis used is data collection, data reduction, data presentation and drawing conclusions. The results of the study show that (1) the implementation of fiqh learning based on the yellow book of mukhtasar abi suja in grade VIII students at MTs Darun Najah has a positive impact on students because learning is more effective and efficient. Which this learning is divided into 3 stages, namely planning which includes learning goal planning, learning material planning, learning strategy planning, learning media planning. The implementation is divided into activities, namely the beginning, core, and end or closing activities. and evaluation. The a. supporting factors for this implementation are the principal's policy, Diniyah School, Qira'atul Kutub Subjects. and b. inhibiting factors are boredom and lack of time. The consequences of this learning are a. learning to be effective and efficient, b. increase in student achievement, and c. increase in student scores.